Revision of the genus Cnemaspis Strauch, 1887 (Sauria: Gekkonidae), from the Mentawai and adjacent archipelagos off western Sumatra, Indonesia, with the description of four new species - Das, I. (The Society for the Study of Amphibians and Reptiles, 2005)
Four new species of Cnemaspis are described from the Mentawai and adjacent archipelagos along the northwest to the southwest coast of Sumatra, Republic of Indonesia, and one each from Simeulue, Nias, Siberut, and Enggano. These populations were allocated by earlier workers to Cnemaspis kandiana (Kelaart, 1852), a Sri Lankan highland endemic. The high levels of endemicity of the fauna of these islands have been attributed to their geographical isolation, historical lack of aridity, and effects of glacial emergence of the Sunda Shelf caused by its maritime climate.